PERKEMBANGAN SOSIAL ANAK USIA 7-11 TAHUN DI JALAN NILAM GANG KARYA KELURAHAN SUKARAMAI KECAMATAN PEKANBARU KOTA - Febrianti, Indria; Sumardi, Sumardi; Widiastuti, Widiastuti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstrack: How high is the social development of children aged 7-11 at Jalan Nilam Gang Karya, Sukaramai Village, Pekanbaru City District? The benefits of giving up disagreeable thoughts about the social development of children aged 7-11 at Jalan Nilam Gang Karya, Sukaramai Village, Pekanbaru City District. This research is descriptive with a quantitative approach. The population in this study was 30 people. Saturated samples were used for sampling in this study. The instrument used was a questionnaire with 37 item statements. The social development of children aged 7-11 on Jalan Nilam gang Karya in the village of Sukaramai, Pekanbaru City District was measured using indicators (1) that established relationships with families (2) relationships with peers (3) relationships with the wider community. The results of the study reveal that the social development of children aged 7-11 at Jalan Nilam gang Karya, Sukaramai Village, Pekanbaru City, is relatively good. The indicator is very good at entering into a relationship with a family of 80.75%, an indicator of a relationship with peers at 78%, an indicator of having a relationship with the community 69.27% is considered good . It can therefore be said that most children aged 7 to 11 have good social development with regard to establishing relationships with family, peers and the wider community.Key Words: Development, Social, Children From 7-11 Years